Exploring the impression of university students on "Teaching Camp" based on "Free to Learn-Independent Campus" program in developing students' speaking skill - Nurlaela Nurlaela; Idawati Idawati (International Journal of Humanities and Innovation (IJHI), 2022)
The teaching camp is a program during the pandemic. This study aims to explore the university student's impression of the Teaching Camp program that is expected to challenge the university students to connect between universities and the real world or the world of work. This study applied qualitative descriptive research to summarize specific events experienced by individuals or groups of individuals in everyday words. This research was conducted in the Department of English Education, University of Bosowa, Makassar, Indonesia. Four university students participating in the Teaching Camp program were willing to support this study. There are three steps in qualitative analysis in this study using data reduction, data display, and conclusions, namely, to find out the interview answers that have been given to students, then each answer is analyzed using words and according to student answers. This study found that university students have an important role in implementing the ministry of education and culture program. The role referred to here is that university students are the driving force by providing new innovations in learning and being involved in implementing the learning process by teaching literacy and numeracy. Class 1 of the Teaching Camp program enables university students to have an academic and social experience while serving as education facilitators in suburban areas. With so many shortcomings, it is hoped that this first-class Teaching Camp program will become an in-depth evaluation material for the Ministry of Education and Culture and the university.